Meningkatkan Pemahaman Mata Pelajaran Akidah Akhlak Menggunakan Metode Role Playing - Asep Andi Rahman; Sandra Khoirul Ummah (Gunung Djati Conference Series, 2022)
The purpose of this study was to determine (1) students’ understanding of before applying the role playing learning model (2) the implementation of the role playing learning model (3) the result after applying the role playing learning model. The research method used is PTK. Steps of PTK includes: planning, implementation, observation and reflection, this PTK was carried out in two cycles. Data collection tools: observation, tests, interviews and documentation studies. Data analysis uses a simple logical and statistical approach. The result showed that: (1) before the role playing learning model was applied, students’ understanding of the moral aqidah material was: 68,3; (2) the process of applying the method: the teacher mentions the learning material, the teacher makes the student into three groups, the students are selected to act out the drama script, the other students stay in their groups and observe the acting, after the performance is finished each group is given a worksheet for discussion, group representatives presenting the result of the discussion, the teacher conveys general conclusions, and at the end the teacher distributes test questions of student; (3) students’ understanding after the role playing learning model is applied is 83,53 there is an increase in understanding of 15,23. Thus, it can be concluded that the application of the role playing leraning model is able to improve the understanding of moral aqidah subjects in class VIII students with the material “The negative impact of hasad, revenge and backbiting”, this is evidenced by the number of students being able to answer some of the questions or quations given.